The Paradigm of Recognition : Freedom as Overcoming the Fear of Death. - Cobben, Paul. (Critical Studies in German Idealism, 2012)
In The Paradigm of Recognition. Freedom as Overcoming the Fear of Death Paul Cobben defends the position that Hegel's Phenomenology of Spirit contains all the building blocks to elaborate a paradigm of recognition which fundamentally criticizes the contemporary versions of Habermas, Rawls and Honneth. In his concept of recognition, the fear of death is the central category to understand the mediation between freedom and nature. Cobben not only systematically reconstructs how this view results from Hegel's criticism of Hume and Kant, but also shows how Hegel's three-part division of social freedom is based on this mediation. Therefore, Honneth wrongly thinks that his three forms of social freedom (related to love, respect and solidarity) correspond to Hegel's three-part division.